Association between serum albumin and cardiovascular diseases among adult population of Kaski district, Nepal - Yadav, Naval Kishor; Pokharel, Daya Ram; Kathayat, Goma; Sigdel, Manoj; Hussain, Imran (Annals of Clinical Chemistry and Laboratory Medicine, 2021)
Background: Serum albumin is an abundant circulatory protein. Several studies were reported that a low level of serum albumin associated with a high risk of cardiovascular diseases (CVDs) mortality. Therefore, the present study aimed to investigate serum albumin levels and find out the association between serum albumin and CVDs and their correlation with cardiovascular risk factors. Methods: This was a cross-sectional study. Patients with confirmed CVDs were enrolled in this study while patients with CVDs plus acute or chronic liver and intestinal diseases were excluded in this study. Data were collected and analyzed by using SPSS version 21. P-value (two-tailed) < 0.05 was considered statistically significant. Results: A total of 400 subjects were enrolled, out of which 200 healthy control (male 125 and female 75) and 200 patients with CVDs (male 130 and female 70). The mean level of total protein, albumin, globulin, and HDL-C were statistically (p<0.005) lower while TC, TG, and FBS were statistically (p<0.005) higher in CVDs sub-jects in compared to healthy control. The serum albumin was lower in 35 (17.5%) of patients with CVDs, out of which 19 (9.5%) were male and 16 (8.0%) were female. Serum albumin showed a statistically significant negative correlation with age (p=0.000) and a positive correlation with TC (p=0.000). In multinomial logistic regression analysis, model-I, II, and III showed a statistically significant (p<0.05) association between serum albumin with CVDs. Conclusion: This study concluded, low serum albumin was found in patients with CVDs and it was significantly associated with CVDs. Therefore, measurement of serum albumin can be performed routinely in patients with CVDs.